Prospective Observational Study Assessing Opioid Addiction Risk in Postoperative Patients Using the Opioid Risk Tool (Ort) At a Tertiary Care Hospital - S, Satish; Sayed, Tasfiya Manzer; Shabaraya, A.R (Asian Journal of Pharmaceutical Research and Development, 2025)
Opioids are the narcotic analgesics prescribed to treat persistent and severe pain. An alarming increase in opioid misuse in the past two and a half decades has led to a public health crisis. The present study was a prospective observational study conducted in a tertiary care hospital for a period of 6 months. Objective: The study’s primary objective was to determine the potential for opioid addiction among postoperative patients. Methods: Patient individuals aged 18 years and above who underwent surgery and were prescribed opioid analgesics were included in the study. The opioid risk tool (ORT) was used to assess the potential for addiction of opioid drugs. Required information collected from patients, patient parties and medical records. Results: There was a total of 220 patients prescribed with opioids after surgery. Among them 190 were males and 148 were females, which suggests among 220 patients, 18.35% patients were seen to be high potential to opioid addiction, 41.44% were at moderate risk and 35.9% were at low risk of opioid addiction potential. Assessing opioid addiction using opioid risk tool shows apersonal history of substance abuse, alcohol abuse, personal history of depression, family history of substance abuse, and long-term use of opioids are one of the main causes of opioid addiction potential. Conclusion: Opioids are commonly prescribed for post-operative pain management, but prolonged use can lead to the induction of tolerance and the development of dependence. Alternative pain relief methods or pain management plans can be used to reduce opioid misuse and addiction.